Synthesis, Characterization, and Comparative Study on Norbornene Polymerization of CNN and PCN Pincer Palladium Complexes - Huizhu Wang; Jin-Kui Liu; Yi-Dong Wang; Xin-Qi Hao; Mao-Ping Song; Jun-Fang Gong; Hui Jiang (Molecules)
Several CNN pincer Pd(II) complexes including chiral complexes 1a–e with 2-phenyl-6-(oxazolinyl)pyridines and achiral ones 2a–c with N-substituted-2-aminomethyl-6-phenylpyridines were prepared. In addition, the preparation of the achiral PCN pincer Pd(II) complexes 3a–e with aryl-based phosphinite–imine ligands and chiral 4a–c with aryl-based phosphinite–imidazoline ligands was also performed. Among them, the PCN Pd(II) pincers 3a–e were new complexes and were readily synthesized from commercially available materials in only two steps. The new complexes were characterized through elemental analyses, namely 1H NMR, 13C{1H} NMR, and 31P{1H} NMR spectroscopies. Furthermore, the molecular structure of complex 3a was determined via X-ray single-crystal diffraction analysis. In the presence of EtAlCl2, Et2AlCl, or methylaluminoxane (MAO), the CNN pincer Pd(II) complexes and PCN pincer Pd(II) complexes exhibited excellent activities and monomer conversion rates in norbornene addition polymerization. Surprisingly, the CNN pincer Pd(II) complexes exhibited a higher conversion rate (99.5%) with Et2AlCl as the cocatalyst, while the PCN pincer Pd(II) complexes showed a higher conversion rate (98.8%) with MAO.